PHOTOGRAMMETRY: A PROPOSAL OF OBJECTIVE ASSESSMENT OF CHEST WALL IN ADOLESCENT IDIOPATHIC SCOLIOSIS - Alexandre, Anderson Sales; Sperandio, Evandro Fornias; Yi, Liu Chiao; Davidson, Josy; Poletto, Patrícia Rios; Gotfryd, Alberto Ofenhejm; Vidotto, Milena Carlos (Revista Paulista de Pediatria, 2019)
ABSTRACT Objective: To evaluate the chest wall shape in patients with adolescent idiopathic scoliosis (AIS) in comparison to healthy subjects and the association between the chest wall shape with the spine deformity and lung function in patients with AIS. Methods: This cross-sectional study enrolled 30 AIS patients and 20 healthy subjects aged 11-18 years old. The Cobb angle evaluation was performed in AIS patients. The chest wall shape was assessed by the photogrammetry method, using the Postural Assessment Software (PAS). We created thoracic markers shaped as angles (A) and distances (D), as follows: A2 (right acromion/xiphoid/left acromion), A4L (angle formed between the outer point of the smallest waist circumference and its upper and lower edges on the left side), A7 (angle formed by the intersection of the tangent segments of the upper and lower scapulae angles), D1R/D1L [distance between the xiphoid process and the last false rib on the right (R) and left (L) sides], and D3 (distance between xiphoid process and anterior superior iliac spine). Results: The thoracic markers A2 and A7 were significantly higher, while the A4L and D1R/D1L were significantly reduced in the AIS group compared to the control. Moderate correlations were found between: A2 and the main and proximal thoracic Cobb angles (r=0.50, r=0.47, respectively); D1R/D1L and the main thoracic Cobb angle (r=- 0.40); and the forced expiratory volume in the first second (FEV1) and D3R (r=0.47). Conclusions: The photogrammetry method was able to detect chest wall changes in AIS patients, besides presenting correlation between Cobb angles and lung function. RESUMO Objetivo: Avaliar o formato da caixa torácica em pacientes com escoliose idiopática do adolescente (EIA), comparando-os com indivíduos saudáveis e analisar a associação do formato da caixa torácica com a deformidade da coluna vertebral e função pulmonar em pacientes com EIA. Métodos: Estudo transversal que avaliou 30 pacientes com EIA e 20 indivíduos saudáveis com idade entre 11 e 18 anos. O ângulo de Cobb foi avaliado em pacientes com EIA. O formato da caixa torácica foi analisado pelo método da fotogrametria, utilizando o Software para Avaliação Postural (SAPO). Foram criados marcadores torácicos descritos como ângulos (A)e distâncias (D): A2 (acrômio direito/processo xifoide/acrômio esquerdo), A4E (ângulo formado entre o ponto externo da menor circunferência da cintura e suas bordas superior e inferior do lado esquerdo), A7 (ângulo formado pela interseção das retas tangentes aos ângulos superior e inferior das escápulas), D1D/D1E [distância entre o processo xifoide e a última costela falsa nos lados direito (D) e esquerdo (E)] e D3 (distância entre o processo xifoide e a espinha ilíaca anterossuperior). Resultados: Os marcadores torácicos A2 e A7 foram significativamente maiores, enquanto o A4E e o D1D/D1E foram significativamente menores no grupo EIA em relação ao controle. Foram encontradas correlações moderadas entre: A2 e os ângulos de Cobb torácico principal e proximal (r=0,50 e r=0,47, respectivamente); D1D/D1E e o ângulo de Cobb torácico principal (r=-0,40); e o volume expiratório forçado no primeiro segundo (VEF1) e D3D (r=0,47). Conclusões: O método da fotogrametria detectou alterações na caixa torácica de pacientes com EIA, além de apresentar correlações significativas entre os ângulos de Cobb e a função pulmonar.